Comparison of different methods by means of which water holding capacity of soil is determined and the prediction of water holding capacity from soil texture in coarse-textured soil - Howell, C. L. (Carolyn Louise) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2004.